WELFARE OR DESPAIR? ITALY AND SPAIN’S DIVERGING WELFARE STATE POLICIES AFTER COVID-19 - Martinus Tejakusuma; Reza Triarda (Indonesian Association for International Relations, 2025)
The objective of this study is to investigate how right-wing populist parties influenced post-pandemic welfare state policy shifts, particularly in family welfare, gender equality, and immigration. This research utilizes right-wing populism and welfare state regime theories. Employing a Most Similar Systems Design (MSSD) and a qualitative comparative case study approach, this research analyzes policy changes from 2020-2024 using secondary data. Findings indicate that Italy, under right-wing populist governance, adopted exclusionary policies, reinforced traditional family structures, and restricted migrant access to social benefits. Conversely, Spain’s governance expanded social protections, promoting inclusive gender policies and migrant integration. The study concludes that right-wing populism significantly shaped divergent welfare state responses in these comparable Southern European contexts.